2020
DOI: 10.1177/1756284820937115
|View full text |Cite
|
Sign up to set email alerts
|

High dose PPI-amoxicillin dual therapy for the treatment of Helicobacter pylori infection: a systematic review with meta-analysis

Abstract: Background: Helicobacter pylori resistance to amoxicillin remains rare in many regions. Proton pump inhibitor-amoxicillin-containing high dose dual therapy (HDDT) has been proposed to treat H. pylori infection. We aimed to assess the effectiveness and safety of PPI-amoxicillin HDDT for treatment of H. pylori infection in comparison with other regimens. Methods: Databases, including PubMed, Embase, and the Cochrane Register of Controlled Trials, were searched to find relevant publications. Randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 49 publications
3
59
0
4
Order By: Relevance
“…Meta-analyses reported that the efficacy of HDDT was comparable to recommended firstline or rescue therapies for H. pylori infection with fewer adverse effects. [42][43][44] Unfortunately, patients allergic to penicillin, and the potentially rare but intolerable side effects of furazolidone have limited their widespread application. Meanwhile, TET is not available in most area in China.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses reported that the efficacy of HDDT was comparable to recommended firstline or rescue therapies for H. pylori infection with fewer adverse effects. [42][43][44] Unfortunately, patients allergic to penicillin, and the potentially rare but intolerable side effects of furazolidone have limited their widespread application. Meanwhile, TET is not available in most area in China.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, testing for high-dose dual therapy as rescue therapy in Italy is urged in order to increase the ‘weapons in our therapeutic armamentarium’. Indeed, such a therapy might be introduced before rifabutin, aiming to limit the use to avoid bacterial resistance, when considering its usefulness for tuberculosis treatment in AIDS patients and its potential use for multidrug-resistant pathogens such as the so-called ESKAPE organisms (an acronym for Enterococcus faecium, S. aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa , and Enterobacter species) [ 58 ]. In conclusion, data obtained through our literature review found that standard therapies for H. pylori eradication can be used when following an appropriate sequence, allowing clinicians to improve the cure rate without resorting to bacterial culture.…”
Section: Discussionmentioning
confidence: 99%
“…While the standard-dose PPI-amoxicillin dual therapy gave disappointing eradication rates (for review, see [149]), stronger and long-lasting acid suppression (achieved with multiple doses of the antisecretory drug) appeared to be successful. Three meta-analyses [150][151][152] collected all the studies with high-dose PPI-amoxicillin combinations, which showed that this dual therapy is as effective as triple or bismuth-based quadruple therapy, either in first-line or rescue treatment. In addition, compliance with dual therapy was better and the adverse event rate lower [150][151][152].…”
Section: Efficacy Of Vonoprazan-based Eradication Regimensmentioning
confidence: 99%